The runaway bunny - Brown, Margaret Wise, 1910-1952.; Hurd, Clement, 1908-1988 (New York : Scholastic)
A little rabbit who wants to run away tells his mother how he will escape, but she is always right behind him.
"A Trumpet Club special edition."
Reprint. Previously published: New York : Harper & Row, 1972.
Keywords: Rabbits -- Fiction